Conversion of Organic Waste to Novel Adsorbent for Fluoride Removal: Efficacy and Mechanism of Fluoride Adsorption by Calcined Venerupis philippinarum Shells - Choi, Moon Yeong; Lee, Chang Gu; Park, Seong Jik (Water, Air, and Soil Pollution, 2022)
Venerupis philippinarum shells (VPSs), which are composed mainly of CaCO3, have been considered for use as a fluoride adsorbent because of their high Ca content and low processing cost and the opportunity for waste reuse. VPSs were calcined at various temperatures (100, 300, 500, 700, 800, and 900 °C), and those calcined at 800 °C (VPS-800) and 900 °C showed the highest fluoride adsorption capacity. As the calcination temperature increased, the CaCO3 in the VPSs changed to CaO and Ca(OH)2, and the solubility of Ca increased owing to a change in crystalline phase, enabling fluoride adsorption by the VPSs. The adsorption of fluoride by VPS-800 followed the Freundlich equilibrium model and pseudo-second-order kinetic model, and the maximum fluorine adsorption capacity was 301.87 mg/g. The maximum adsorption efficiency at an adsorbent dose of 5 g/L in a 700 mg/L fluoride solution was 99.5%. The enthalpy and entropy were 34.76 kJ/mol and 140.13 J/mol‧K, respectively, and the change in the Gibbs free energy was negative at all reaction temperatures. Fluoride adsorption by VPS-800 was favored at low pH (pH 3), and it was slightly affected by pH at pH 5–11. The anion competition effect followed the order HPO42− > HCO3− > SO42− > Cl−. VPS-800 is an eco-friendly adsorbent obtained by simple heat treatment of waste and is effective in removing fluoride. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Adsorption capacities; Ca-based adsorbent; Fluoride adsorptions; Fluoride removal; Organic wastes; Processing costs; Seashell; Thermal activation; Venerupi philippinarum shell; Waste reuse; Ca-based adsorbent; Calcination; Fluoride removal; Seashells; Thermal activation; Venerupis philippinarum shells